Entrepreneurships in times of crisis and the digitalization of Mypes with Covid 19 - Acevedo, Jesus Enrique Reyes (Eximia, 2022)
In the present investigation, the aspects of the digitalization of business organizations (Mypes) are analyzed in a social, economic and political situation in which many elements and aspects of our national economy are restricted due to the health emergency caused by COVID. 19 We will address the issue by presenting the national economic background that occurred in Peru, caused by the health crisis, which motivated companies to seek other alternative solutions, since digitalization was consolidated as a response that revolutionized our entire reality. In addition, the importance of medium and small companies within our economy is highlighted, and their digital transformation process, in the same way we address the process of implementing digital marketing and the use of digital tools. The digitalization of the different types of ventures by necessity or opportunity generated by the health pandemic and the impact of technological means are also taken into consideration, together with the commercial and business strategies developed by MYPES. In another context, the state programs that support the digitization of MYPES are explained, followed by the conclusions reached, as a result of the systematic research that I develop in this document.